Reformar el artículo 278 del código orgánico integral penal, respecto a la incapacidad permanente para ejercer cargo público - Rodriguez Dalgo, Byron Fabricio (2016)
Modern penal doctrine, tends to follow the current minimum criminal law where the State requires the use of criminal law as a measure of last resort and within this current if required by the State the right to punish, this should apply the principle of proportionality between offenses and criminal sanctions. The Constitution of the Republic of Ecuador in Article 195 establishes the exclusive power of the Attorney General of the State to exercise public criminal action, but, in that article also provides that the principles of opportunity and minimum penal intervention must be observed; . In Article 76 paragraph 6 of the constitutional provision requires the application of the principle of proportionality between the offense and the criminal sanction; that is, the current constitution is in the same line of modern doctrinaire current criminal. These rights, are intended to ensure the social reintegration of persons deprived of liberty and who have complied with the sentence that was imposed upon them, in other words have paid their debt to society, however there is a contradiction between Articles 278 and 53 of the Code Integral Penal, when in the first, is sentenced to the subject of crimes of embezzlement not hold public office for life, while Article 53 of the same Act states that indefinite sentences are banned. This is one of the main reasons that led me to conduct a more thorough analysis of the requirements prescribed in Articles 53 and 278 of the Code Integral Criminal, considering also that from a constitutional point of view, it would be nugatory rights prisoners social reintegration, the right to work because of his criminal record. At present a person who has been sentenced for the crime of embezzlement, despite having served his sentence, can not choose any public or private office in financial institutions throughout his life, because one of the requirements for getting a job is not have been sentenced for embezzlement, a situation that causes a strong stigma because it limits their social and professional reintegration, affects their psychological and moral integrity to see that job opportunities are closed. It may not be possible or just a person who has been convicted of murder, murder, rape among other serious crimes, although most dangerous have the opportunity to exercise any public office or financial institutions, thus fulfills the State social reintegration to work and non-discrimination; however, people who have met with imprisonment for the crime of embezzlement not have that opportunity. So it is necessary to reform the Art. 278 of the Code Integral Criminal so that the sanction of inability to perform public or financial institutions charge, be repealed, and given treatment legality of the penalty equal rights to all offenders other crimes.